Peripartum Cardiomyopathy: A Case Management Series At Sanjiwani Hospital - Eva, Grace; Raka Budayasa, Anak Agung Gede; Indrayana Putra, Anak Agung Gede; Bagiari, Ketut Erna (Fakultas Kedokteran Universitas Andalas, 2023)
Introduction: In Peripartum Cardiomyopathy (PPCM), heart function will generally return to normal a fewmonths after delivery, but in some cases poor outcomes might occur, therefore early detection and managementare crucial. This case series study aims to get an overview of PPCM cases in a type-B referral hospital in Gianyar,Bali.Case Presentation: This study presents 3 cases of PPCM that showed symptom onset in the antepartum period(the third trimester of pregnancy). Two out of three cases were nulliparous with maternal age <30 years, andwent through a Cesarean Section. All three cases underwent treatment in the Intensive Care Unit and showedimprovement in their condition.Discussion: Until now, the heterogeneity of PPCM diagnostic criteria has become an obstacle to its treatment,thus the reported incidence tends to be low. This is likely due to the diagnosis of PPCM which is an exclusiondiagnosis from other causes of heart failure. Echocardiography and NT-ProBNP examinations should be done,which, although not specific, may lead to a diagnosis of PPCM when combined with a thorough patient history.The availability of supporting examination modalities in many regions in Indonesia are varied thus referrals areusually needed, resulting in the delay of PPCM cases management.Conclusion: All pregnant women who experience dyspnea during the third trimester of pregnancy, along with afamily history of heart disease, need to undergo close examination and supervision due to the suspicion of PPCM.Early detection and treatment are the main key to successful management of PPCM cases